Feasibility of implementing intervention methods in an adolescent worksite tobacco control study. (26th November 2003) - Hunt, M K; Fagan, P; Lederman, R; Stoddard, A; Frazier, L; Girod, K; Sorensen, G
Abstract : Objective: To present feasibility data on SMART, the first teen worksite behavioural tobacco control intervention. Design: This phase II study was designed to estimate the efficacy and feasibility of a small scale, randomised, controlled intervention. Setting and subjects: This study, addressing youths aged 15–18 years, was implemented in four intervention and five control grocery stores that had an average of 44 eligible teens. Interventions: The tobacco use cessation and prevention interventions were based on social influences and peer leader models. Employee break rooms served as centres both for interactive activities including open houses, teen advisory boards, peer leader interviews, games and contests; and non-interactive interventions including bulletin boards and table tents with health messages and home mailings. Main process measures: Project staff collected process data on the extent of implementation of intervention activities, participation rates in activities, and contacts with peer leaders. On the final survey, teens reported on awareness of, participation in, and motivation for participating in project activities. Results: Indicators of feasibility were identified and discussed, including the number of activities implemented, teen participation, management support, cost, and barriers to and facilitators of implementation. During the 12 month intervention, a mean of 24.1 interactive activities and 55.3 non-interactive activities were implemented, and a mean 14.2% participation rate per activity per site was achieved. Eighty four per cent of teens reported being aware of SMART, and 39% reported participating in interactive and 67% in non-interactive activities. Conclusions: Teen smoking cessation rates in worksite programmes might be improved if they are conducted in companies where there is job stability and if teen programmes are part of worksite-wide tobacco control programmes that include both teens and adults.